Interface instabilities in polymer light emitting diodes due to annealing - Janssen, Franciscus Johannes Joseph; Sturm, J. M.; Denier van der Gon, A. W.; IJzendoorn, Leo J. van; Kemerink, Martijn; Schoo, H. F. M.; de Voigt, Martien J. A.; Brongersma, Hidde H. (Organic electronics, 2003)
In polymer light emitting diodes (PLEDS) with an (ITO/PPV/Ca) structure we observed a significant reduction of both the current and the light output at constant voltage after heat treatment for only 30 min at 65 °C. Electroluminescence spectroscopy experiments showed that the shape as well as the amplitude of the spectra were changed. The reduction of current and light output was investigated by measuring I-V and E-V (current-voltage and brightness-voltage) characteristics of PLEDs, I-V characteristics of single carrier devices, and by performing low energy ion scattering and X-ray photoelectron spectroscopy experiments on the Ca/PPV interface. It was concluded that the current and light output reduction could be ascribed to the degradation of the Ca/PPV and the ITO/PPV interfaces. The degradation of the ITO/PPV interface resulted in a reduction of the zero field hole mobility and a small increase of the field dependence of the mobility. The degradation of the Ca/PPV interface, probably by diffusion of calcium into the PPV, resulted in carrier traps and quenching sites, which influenced the field dependent electron mobility.